Dejavniki neizvedene zdravstvene nege - Bahun, Mateja (Obzornik zdravstvene nege, 2021)
Introduction: Missed nursing care is a concept that is emerging in patient healthcare around the world. The purpose of a systematic literature review is to describe missed nursing care and gain an understanding of the connection between the concept and the factors for its emergence.Methods: A systematic literature review was conducted in February and March 2020 in databases PubMed, CINAHL, Wiley library online, COBISS.SI. The search terms were: unfinished nursing care, missed nursing care, implicit rationing, care left undone. The search strategy was based on inclusion criteria: scientific journals, peer-reviewed publications, full text, the Slovenian or English language, period 2015%2020. The results were analyzed with a thematic analysis.Results: A total of 1,667 articles were identified and 16 were included in the final analysis. Of these, there were two systematic literature reviews, twelve cross-sectional studies, and two descriptive quantitative studies, bringing together the results of 88,294 nursing staff from 21 countries. The results showed three groups of factors for missed nursing care: staffing characteristics, characteristics of the work environment and teamwork with communication.Discussion and conclusion: The results show that the causes for missed nursing care are complex and inconsistent. They differ between countries also due to different nursing educational systems. They are related to factors in a health care organization and the characteristics of nurses. If we want to determine the quantity and scope of missed nursing care at the national level, specific data regarding this area in Slovenia is needed.
Keywords: medicinske sestre; missed nursing care; neizvedena zdravstvena nega; nurses; racionalizacija; rationing; zdravstvena nega